2012
DOI: 10.1192/bjp.bp.111.098079
|View full text |Cite
|
Sign up to set email alerts
|

Structure of major depressive disorder in adolescents and adults in the US general population

Abstract: BackgroundAlthough techniques such as latent class analysis have been used to derive empirically based subtypes of depression in adult samples, there is limited information on subtypes of depression in youth.AimsTo identify empirically based subtypes of depression in a nationally representative sample of US adolescents, and to test the comparability of subtypes of depression in adolescents with those derived from a nationally representative sample of adults.MethodRespondents included 912 adolescents and 805 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
76
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 53 publications
6
76
1
Order By: Relevance
“…In particular, the typical subtype was characterized by more loss of appetite and weight loss, psychomotor change and feelings of guilt, while the atypical tended to be defined by increased appetite and weight gain along with increased rates of binge eating disorder and higher body mass index (BMI). 70 Collectively, the findings from these studies suggest both symptom type and severity are sources of heterogeneity in adolescent depression and anxiety. Compared to adults, behavioral and somatic symptoms may be more common, and psychomotor symptoms less.…”
Section: -74mentioning
confidence: 89%
See 4 more Smart Citations
“…In particular, the typical subtype was characterized by more loss of appetite and weight loss, psychomotor change and feelings of guilt, while the atypical tended to be defined by increased appetite and weight gain along with increased rates of binge eating disorder and higher body mass index (BMI). 70 Collectively, the findings from these studies suggest both symptom type and severity are sources of heterogeneity in adolescent depression and anxiety. Compared to adults, behavioral and somatic symptoms may be more common, and psychomotor symptoms less.…”
Section: -74mentioning
confidence: 89%
“…57 Because LCA identifies subclasses that share common characteristics, this method provides different information than variable-level techniques and may be more relevant to mental health treatment, prevention, practice, and policy. 69,70 While the preponderance of studies using LCA to examine subtypes of depression three anxiety problem classes and four affective problem classes. 68 Similarly, in a sample of 2,539 13-18 year olds from the NCS-A, Burstein et al also identified seven classes of adolescents with lifetime anxiety disorders that were characterized by disorder type rather than the degree or number of disorders.…”
Section: -74mentioning
confidence: 99%
See 3 more Smart Citations